2021
DOI: 10.3389/fonc.2021.693002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Disease 2019 on Clinical Characteristics in Patients With Lung Cancer: A Large Single-Centre Retrospective Study

Abstract: Lung cancer is the most common cancer malignancy worldwide. With the continuous spread of the coronavirus disease 2019 (COVID-19) globally, it is of great significance to explore the impact of this disease on the clinical characteristics of lung cancer. Thus, we aimed to investigate whether the COVID-19 pandemic had any influence on the clinical characteristics and diagnosis of patients with lung cancer. We collected clinical and demographic data of patients who were newly diagnosed with lung cancer at our hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The prevention and control policies for controlling the spread of the virus taken by hospitals have played a positive role but have also impacted the treatment of other diseases. Cancer patients are of particular concern because they especially need timely treatment and diagnosis ( 7 ). Mounting evidence shows that the diagnosis and treatment of cancer were delayed during the pandemic ( 8 ), which may increase the likelihood of cancer metastasis or lead to progression from a curable to an incurable state ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevention and control policies for controlling the spread of the virus taken by hospitals have played a positive role but have also impacted the treatment of other diseases. Cancer patients are of particular concern because they especially need timely treatment and diagnosis ( 7 ). Mounting evidence shows that the diagnosis and treatment of cancer were delayed during the pandemic ( 8 ), which may increase the likelihood of cancer metastasis or lead to progression from a curable to an incurable state ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, it was found that the average age of lung cancer during the pandemic period was younger. In a study conducted in China during the pandemic, lung cancer patients during the pandemic were significantly younger 12 . Curfews over the age of 65 and fear of infection may have an impact on hospital admissions.…”
Section: Discussionmentioning
confidence: 96%
“…The pandemic did not change the lung cancer metastasis rates of patients. In similar studies, the pandemic did not cause major stage changes in lung cancer [10][11][12] .…”
Section: Discussionmentioning
confidence: 98%
“…In the United Kingdom, referrals for cancer-suspected cases decreased by about 80% (7,17). The potential causes of these delays in diagnosis and treatment are the limitations in hospital resources and the hesitancy of patients to receive necessary health care services during the COVID-19 pandemic (18,19). According to a study of lung cancer patients who participated in clinical trials during the SARS outbreak, 64% of patients were hesitant to visit a hospital due to fear of infection, and 4% of patients decided to cease all treatment because of infection issues.…”
Section: Discussionmentioning
confidence: 99%